COMPARATIVE CHARACTERISTICS OF THE EFFECT OF SOME INDUSTRIALLY SIGNIFICANT MEDICINAL HERBS ON THE CARDIOVASCULAR AND LYMPHATIC SYSTEMS OF AN AGING ORGANISM - Demchenko Georgii Anatolevish; Tuleuchanov SultanTuleuchanovish; Nurmakhanova Bayan Abdisalamkyzy; Imankulova Sofia; Boranbayeva Gulsaya; Аbdreshov Serik Nauryzbaevich; Makashev E.K. (Academic Journal of Physical and Chemical Sciences, 2021)
The purpose of this study was to identify the corrective properties of a number of medicinal herbs for age-related changes in the aging body. In an experimental study on 8 groups of old animals, a number of medicinal herbs of the Kazakh flora were studied: Ziziphora Bunge, Almaty hawthorn, St. John’s wort, Echinacea purpurea, kopeechnik, badan thick-leaved on the parameters of the cardiovascular and lymphatic systems. All the medicinal herbs tested by us affected the animal body to some extent and, according to the studied indicators, showed a positive effect in the direction of a younger organism. There was an increase in lymph flow, diuresis, weight loss, changes in the indicators of swellability, blood and lymph viscosity, blood pressure and heart rate. The data from the screening study allowed us to further combine them into a phytocomposition for subsequent studies in order to correct changes in the old body.